Studies on Effect of Temperature on Asphaltene precipitation using Multi Stage Extraction - Chandrika, Kethineni; Sampath, N; V J, Jobin; Seetha Ramaiah, E; Vipin, Vishnu; S F, Choragudi (International Journal of Engineering and Technology, 2017)
In the case of asphaltene extraction, single stage extraction given a maximum yield at 30Â°c with the sample to solvent ratio of 1:25. The time taken for the extraction process is 24 hours. In the case of long step extraction process its sample to ratio is 1:4. When the temperature increased in the process the yield also started increasing. The maximum yield we could get in the temperature range of 30Â°c to 50Â°c. It is possible to reduce the extraction time by increasing the temperature and it gives a good yield of asphaltene with the usage of multistage process. It increased the asphaltene presence about 69% in the solvent. The asphaltene yield at 30Â°c give raise an extraction of 85% in a six-stage extraction process. It is possible to get the same extraction percentage in a temperature of 50Â°c with three stage extraction process.Â Â